2002
DOI: 10.1152/ajpheart.00324.2002
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil (Viagra) induces powerful cardioprotective effect via opening of mitochondrial KATPchannels in rabbits

Abstract: Sildenafil citrate (Viagra) is the pharmacological agent used to treat erectile dysfunction in men. Because this drug has a vasodilatory effect, we hypothesized that such an action may induce a preconditioning-like cardioprotective effect via opening of mitochondrial ATP-sensitive K (K(ATP)) channels. Rabbits were treated with sildenafil citrate (0.7 mg/kg iv) either 30 min (acute phase) or 24 h (delayed phase) before 30 min of ischemia and 3 h of reperfusion. Mitochondrial K(ATP) channel blocker 5-hydroxydeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
240
3
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 275 publications
(277 citation statements)
references
References 32 publications
(29 reference statements)
21
240
3
13
Order By: Relevance
“…Whereas the involvement of the mK ATP channels has been demonstrated for the cardioprotective effect of sildenafil, the possibility of the same mechanism of action being involved for the tadalafil effect, at least in view of our results, will require further investigation. 10,13 It has been suggested that elevated levels of cGMP, caused by PDE5 inhibitors, could inhibit PDE3, an enzyme responsible for the hydrolysis of cyclic adenosine monophosphate (cAMP) and increase cAMP levels, resulting in elevated HR and contractility. 19 Our results showed that tadalafil did not increase HR nor induce arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the involvement of the mK ATP channels has been demonstrated for the cardioprotective effect of sildenafil, the possibility of the same mechanism of action being involved for the tadalafil effect, at least in view of our results, will require further investigation. 10,13 It has been suggested that elevated levels of cGMP, caused by PDE5 inhibitors, could inhibit PDE3, an enzyme responsible for the hydrolysis of cyclic adenosine monophosphate (cAMP) and increase cAMP levels, resulting in elevated HR and contractility. 19 Our results showed that tadalafil did not increase HR nor induce arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Recent studies have shown that these medicines improve endothelial function and may also have vascular and myocardial protective effects. [10][11][12][13] Tadalafil differs from sildenafil and vardenafil by its pharmacokinetic profile, 17.5 h half-life, maximum plasma concentration at 2 h and efficacy for up to 36 h after dosing. 14 As there is no previous information on tadalafil in the setting of myocardial infarction, we studied the effects of tadalafil on infarct size (IS), hemody-namics and regional myocardial blood flow (RMBF) after myocardial ischemia and reperfusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The present study demonstrates the protective effect of a longer acting PDE-5 inhibitor suggesting that the differences in half-life of the three PDE-5 inhibitors has little, if any impact on the cardioprotective effect, at least during the acute time-window of treatment 30 min before I-R. The degree of infarct size reduction was, however, lower with tadalafil (B22%) 1 as opposed to sildenafil (68%) 3 or vardenafil (58%) 4 in rabbits as reported previously from our laboratory. These differences may be attributed to the animal species studied (rat versus rabbit) or lower potency of tadalafil (IC 50 6.74 nM) as compared to sildenafil (IC 50 3.5 nM) and vardenafil (IC 50 0.14 nM).…”
mentioning
confidence: 58%
“…2 In 2002, we first reported a powerful protective effect of sildenafil against myocardial infarction in a rabbit model of I-R in vivo. 3 Since then, several laboratories across the world reproduced these findings in various animal models of I-R injury as summarized in Table 1. Moreover, a recent study from our laboratory showed that vardenafil (Levitra), another potent PDE-5 inhibitor, was equally effective as sildenafil in reducing infarct size following I-R injury in rabbits.…”
mentioning
confidence: 97%